2009
DOI: 10.1057/jibs.2008.106
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-sharing and social interaction within MNEs

Abstract: Social interaction between managers from different units of a multinational enterprise (MNE) has been shown to be an important factor stimulating intra-MNE knowledge-sharing. Face-to-face social interactions form a communication channel particularly conducive to the transfer of tacit, non-codified knowledge. But intensive social interaction also provides opportunities for social construction of knowledge in a learning dialogue. The first explanation (sender–receiver) makes us expect social interaction to moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
257
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(264 citation statements)
references
References 79 publications
4
257
2
1
Order By: Relevance
“…Fundamentally, knowledge flows depend on human interactions and people"s abilities to transfer knowledge Argote, Ingram, Levine, & Moreland, 2000;Argote, McEvily, & Reagans, 2003;Noorderhaven & Harzing, 2009): it is not units as such that exchange knowledge, but individuals within those units. Previous studies that examined MNC knowledge flows from the perspective of the individual focused for example on expatriates (Bonache & Zárraga-Oberty, 2008;Crowne, 2009;Engelhard & Nägele, 2003;Hocking, Brown, & Harzing, 2004, 2007Lazarova & Tarique, 2005), knowledge workers (Sunaoshi, Kotabe, & Murray, 2005) or general knowledge sourcing efforts within MNCs (Teigland & Wasko, 2009).…”
Section: Mnc Knowledge Flows At the Individual-level: The Central Rolmentioning
confidence: 99%
“…Fundamentally, knowledge flows depend on human interactions and people"s abilities to transfer knowledge Argote, Ingram, Levine, & Moreland, 2000;Argote, McEvily, & Reagans, 2003;Noorderhaven & Harzing, 2009): it is not units as such that exchange knowledge, but individuals within those units. Previous studies that examined MNC knowledge flows from the perspective of the individual focused for example on expatriates (Bonache & Zárraga-Oberty, 2008;Crowne, 2009;Engelhard & Nägele, 2003;Hocking, Brown, & Harzing, 2004, 2007Lazarova & Tarique, 2005), knowledge workers (Sunaoshi, Kotabe, & Murray, 2005) or general knowledge sourcing efforts within MNCs (Teigland & Wasko, 2009).…”
Section: Mnc Knowledge Flows At the Individual-level: The Central Rolmentioning
confidence: 99%
“…In contrast, teams with a high level of social interaction did not significantly perform application capacity better than those teams with other conditions of social interaction. These findings reflect that a high level of social interaction provides synchrony and bandwidth (Noorderhaven & Harzing, 2009) for parallel and simultaneous information to enhance the capacity in assessment and assimilation, but the advantage of synchrony and bandwidth does not enhance capacity in application. This result should not be surprising because the knowledge of application in product design and sales service teams can be associated with functional specialty, i.e., computer programming language, database, and interface design, thereby, the condition of physical proximity has no direct impact on exploiting the new knowledge.…”
Section: Discussionmentioning
confidence: 85%
“…Nonaka and Takeuchi (1995) emphasized that knowledge transferring can be better conducted via a more direct and natural routine for both socialization and internalization. Noorderhaven and Harzing (2009) indicated that communication intensity and bandwidth enhance social interaction, and argued that social interactions under rich communication media facilitate the movement of knowledge. The communication setting that provides wider bandwidth and better synchrony allows parallel information for simultaneous interactions.…”
Section: Prediction Based On Condition Of Social Interactionmentioning
confidence: 99%
“…MNE knowledge flows may occur in multiple directions, vertically between the HQ and a subsidiary, and horizontally between different subsidiaries (Noorderhaven & Harzing, 2009;Yang et al, 2008). However, while subsidiaries' contributory roles depend on a specific set of subsidiary resources or the overall MNE strategy (e.g., Birkinshaw, Hood, & Jonsson, 1998), virtually all subsidiaries receive knowledge from HQ.…”
Section: Theoretical Backgroundmentioning
confidence: 99%